SSL5-AnxA5 Fusion Protein Constructed Based on Human Atherosclerotic Plaque scRNA-Seq Data Preventing the Binding of Apoptotic Endothelial Cells, Platelets, and Inflammatory Cells - Yifei Zhao; Xingyu He; Teng Hu; Tianli Xia; Fangyang Huang; Changming Li; Yiming Li; Fei Chen; Mao Chen; Jun Ma; Yong Peng (Biomedicines)
Background and aims: Coronary obstruction following plaque rupture is a critical pathophysiological change in the progression of stable angina (SAP) to acute coronary syndrome (ACS). The accumulation of platelets and various inflammatory cells on apoptotic endothelial cells is a key factor in arterial obstruction after plaque rupture. Through single-cell sequencing analysis (scRNA-seq) of plaques from SAP and ACS patients, we identified significant changes in the annexin V and P-selectin glycoprotein ligand 1 pathways. Staphylococcal superantigen-like 5 (SSL5) is an optimal antagonist P-selectin glycoprotein ligand 1 (PSGL1), while annexin V (AnxA5) can precisely detect dead cells in vivo. We constructed the SSL5-AnxA5 fusion protein and observed its role in preventing the interaction between apoptotic endothelial cells, platelets, and inflammatory cells. Methods: The scRNA-seq data were extracted from the Gene Expression Omnibus (GEO) database. Single-cell transcriptome analysis results and cell–cell communication were analyzed to identify the ACS and SAP cell clusters and elucidate the intercellular communication differences. Then, we constructed and verified a fusion protein comprising SSL5 and AnxA5 domains via polymerase chain reaction (PCR) and Western blot. The binding capacity of the fusion protein to P-selectin and apoptotic cells was evaluated by flow cytometry and AnxA5-FITC apoptosis detection kit, respectively. Furthermore, co-incubation and immunofluorescence allowed us to describe the mediation effect of it between inflammatory cells and endothelial cells or activated platelets. Results: Our analysis of the scRNA-seq data showed that SELPLG (PSGL1 gene) and ANNEXIN had higher information flowing in ACS compared to SAP. The SELPLG signaling pathway network demonstrated a higher number of interactions in ACS, while the ANNEXIN signaling pathway network revealed stronger signaling from macrophages toward monocytes in ACS compared to SAP. Competition binding experiments with P-selectin showed that SSL5-AnxA5 induced a decrease in the affinity of PSGL1. SSL5-AnxA5 effectively inhibited the combination of endothelial cells with inflammatory cells and the interaction of activated platelets with inflammatory cells. Additionally, this fusion protein exhibited remarkable capability in binding to apoptotic cells. Conclusions: The bifunctional protein SSL5-AnxA5 exhibits promising potential as a protective agent against local inflammation in arterial tissues, making it an excellent candidate for PSGL1-related therapeutic interventions.